Unraveling the Role of N6-Methyladenosine in Prostate Cancer: Implications for Prognosis and Tumor Aggression - Xu, Xin; Zheng, Xinqiao; He, Housheng (Serican Journal of Medicine, 2025)
The epitranscriptomic modification N6-methyladenosine (m6A) has emerged as a central regulator of RNA metabolism, influencing diverse physiological and pathological processes. As the most abundant RNA modification in eukaryotic cells, m6A dynamically modulates gene expression by regulating RNA processing, stability, and translation. Dysregulation of m6A has been implicated in key oncogenic processes, including tumor initiation, progression, metastasis, therapy resistance, and interactions within the tumor microenvironment. Despite these advances, the role of m6A in prostate cancer remains poorly understood, highlighting the need for further investigation. In a recent study, Xu et al. utilized refined m6A meRIP-seq to profile 162 primary prostate cancer patient samples, unveiling novel insights into the epitranscriptomic landscape of this malignancy. These findings not only enhance our understanding of m6A regulation in cancer biology but also underscore its potential to inform diagnostic, prognostic, and therapeutic strategies for prostate cancer.